Python advanced guide to artificial intelligence : expert machine learning systems and intelligent agents using Python /: expert machine learning systems and intelligent agents using Python. (2018) - Bonaccorso, Giuseppe; Fandango, Armando; Shanmugamani, Rajalingappaa
No abstract available